Cellulose acetate and cellulose acetate compositions
By heterogeneously introducing acetyl groups to specific positions in the glucose ring of cellulose acetate, the biodegradability of cellulose acetate in seawater is enhanced, overcoming the limitations of existing cellulose acetate formulations in marine environments.
Patent Information
- Application Number
- JP2022556298
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-21
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2040-10-21
AI Technical Summary
Cellulose acetate exhibits limited biodegradability in water systems with fewer bacteria than activated sludge, such as seawater, making it unsuitable for marine environments.
The introduction of acetyl groups to the carbon atoms at the 2, 3, and 6 positions of the glucose ring in cellulose acetate, resulting in a total acetyl substitution degree of 1.75 to 2.55, with at least one position having a degree of substitution of 0.7 or less, enhances marine biodegradability.
This approach significantly improves the biodegradability of cellulose acetate in seawater, allowing for effective decomposition even in environments with fewer bacteria, thus addressing the limitations of existing cellulose acetate formulations.
Smart Images

Figure 0007655938000001 
Figure 0007655938000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to cellulose acetate and compositions comprising cellulose acetate. [Background technology]
[0002] In recent years, with the growing interest in the global environment, there has been a demand for biodegradable molded products. Cellulose acetate is a representative example of a biodegradable resin.
[0003] For example, cellulose acetate with a degree of substitution of about 2.5 is used as a material for cigarette filters used in cigarettes including electronic cigarettes, and as a material for absorbents in sanitary products. It is known that cellulose acetate with a degree of substitution of about 2.5 decomposes in soil or activated sludge. However, its biodegradability is not as good as that of cellulose or cellulose acetate with a degree of substitution of 1.8.
[0004] From the viewpoint of improving biodegradability, the degree of substitution of cellulose acetate is preferably low, but a certain degree of acetyl substitution is required for ease of processing by thermoforming, etc. Various studies have been conducted with the aim of improving biodegradability and moldability.
[0005] Patent Document 1 discloses a technique for improving the biodegradability of a polymer such as cellulose ester by adding a basic additive having a pH of 13 or less or 7 or more in a 1% aqueous solution (20° C.).
[0006] Patent Document 2 discloses a technique for reducing the viscosity of a cellulose acylate solution used in a solvent casting method by making the viscosity of the cellulose acylate solution, in which the sum of the acyl substitution degrees at the 2-, 3- and 6-positions is 2.67 or more and the sum of the acyl substitution degrees at the 2- and 3-positions is 1.97 or more, such that -0.1≦(acyl substitution degree at the 3-position−acyl substitution degree at the 2-position)≦0.3. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Special Publication No. 2018-500416 [Patent Document 2] JP 2002-265501 A Summary of the Invention [Problem to be solved by the invention]
[0008] As described above, cellulose acetate is known to be decomposed in soil or activated sludge. However, there is a problem that a satisfactory decomposition rate cannot be obtained in an aqueous system, such as seawater, which has a smaller number of bacteria than activated sludge.
[0009] An object of the present disclosure is to provide a cellulose acetate and a composition having excellent marine biodegradability. [Means for solving the problem]
[0010] Means for Solving the Problems The present inventors, after extensive investigations, have found that by non-uniformly introducing acetyl groups into the carbon atoms at the 2nd, 3rd and 6th positions of the glucose ring, the marine biodegradability of cellulose acetate, even when the total degree of acetyl substitution is relatively high, is significantly improved, and have thus completed the present disclosure.
[0011] That is, the cellulose acetate according to the present disclosure has a total acetyl substitution degree of 1.75 or more and 2.55 or less, and at least one of the acetyl substitution degree at the 2-position and the acetyl substitution degree at the 3-position is 0.7 or less.
[0012] Preferably, the cellulose acetate has a degree of acetyl substitution at the 2-position and a degree of acetyl substitution at the 3-position of 0.7 or less.
[0013] Preferably, the total acetyl substitution degree of this cellulose acetate is 2.00 or more, and more preferably, the total acetyl substitution degree of this cellulose acetate is 2.20 or less.
[0014] The cellulose acetate according to the present disclosure contains any one of the cellulose acetates described above and an additive selected from the group consisting of (a) substances having a pH of 8 or more in a 1% by weight aqueous solution at 20°C, (b) substances soluble in water at 20°C at a concentration of 2% by weight or more, and (c) substances exhibiting biodegradability in seawater.
[0015] Preferably, the content of cellulose acetate in the entire composition is 50% by weight or more, and the total content of additives in the entire composition is 3% by weight or more and 40% by weight or less.
[0016] Preferably, the substance (a) having a pH of 8 or more at 20° C. in a 1% by weight aqueous solution is selected from the group consisting of the following (a1)-(a3): (a1) An inorganic compound containing an oxygen atom bonded to any one of the metal elements Na, K, Ca, or Mg. (a2)Na + , K + , Ca 2+ or Mg 2+ and one or more anions selected from carbonate ions, hydrogen carbonate ions, silicate ions, and aluminate ions. and (a3) Inorganic compounds containing magnesium
[0017] Preferably, the main component of the magnesium-containing inorganic compound (a3) is magnesium oxide.
[0018] Preferably, the substance (b) that is soluble in water at 20° C. at 2% by weight or more is selected from the group consisting of the following (b1)-(b3): (b1) Glycerin ester (b2) Citric acid esters and (b3) Polyethylene glycol having a number average degree of polymerization of 20 or less
[0019] Preferably, the substance (c) that is biodegradable in seawater is a polyester having a weight-average molecular weight of 50,000 or less.
[0020] Preferably, the cellulose acetate composition includes an additive consisting of a combination of magnesium oxide and triacetin. Effect of the Invention
[0021] The cellulose acetate and cellulose acetate composition according to the present disclosure have excellent biodegradability, particularly in seawater. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The present disclosure will be described in detail below based on preferred embodiments. The scope of the present disclosure is not limited to these descriptions, and in addition to the following examples, it is possible to make appropriate modifications and implement the present disclosure without departing from the spirit of the present disclosure. In addition, the present disclosure is not limited to the following embodiments, and various modifications are possible within the scope of the claims. Other embodiments obtained by appropriately combining the technical means disclosed in each of the embodiments are also included in the technical scope of the present disclosure.
[0023] In the present specification, the term "X to Y" indicating a range means "X or more and Y or less." Additionally, unless otherwise noted, "ppm" means "ppm by weight."
[0024] [Cellulose acetate] The cellulose acetate of the present disclosure has a total acetyl substitution degree (DS) of 1.75 to 2.55, and at least one of the acetyl substitution degree at the 2-position (DS2) and the acetyl substitution degree at the 3-position (DS3) is 0.7 or less. This cellulose acetate has excellent biodegradability, particularly in seawater.
[0025] The mechanism of biodegradation of cellulose acetate is explained below. It is believed that biodegradation of cellulose acetate progresses by the action of enzymes that break down cellulose (e.g., β-glucosidase (EC 3.2.1.21) and the like) after each acetyl group of cellulose acetate is hydrolyzed to reduce the degree of substitution. β-Glucosidase is an enzyme that catalyzes the reaction of hydrolyzing the β-glycosidic bonds of sugars. β-Glucosidase is also called β-D-glucoside glucohydrolase and amygdase. When the β-glycosidic bonds that make up the polymer chain of cellulose acetate are hydrolyzed, they become monosaccharides and low molecular weight polysaccharides. Monosaccharides and low molecular weight polysaccharides are decomposed by normal microbial metabolism. Therefore, in order to promote the biodegradation of cellulose acetate, it is effective to promote the removal of the acetyl groups.
[0026] Based on this idea, it was thought that the lower the degree of substitution of the acetyl group in cellulose acetate, the better its biodegradability. This idea is not wrong. However, a low degree of substitution leads to a high melt viscosity and a tendency to thermal decomposition. As a result, it has been difficult to thermoform cellulose acetate with a low degree of substitution.
[0027] Incidentally, hemicellulose, which constitutes wood, contains some acetyl groups. It is known that in broad-leaved trees, these acetyl groups are bound to xylan to form acetyl xylan. This acetyl xylan is also biodegradable. It is known that acetyl xylan esterase (EC 3.1.1.72) exists to decompose acetyl xylan and other substances. Acetyl xylan esterase is an enzyme that catalyzes the deacetylation of xylan and xylooligosaccharides. This enzyme is classified as a hydrolase, and acts particularly on ester bonds.
[0028] It is known that only a few percent of bacteria exist in the ocean compared to those on land. Acetyl xylan esterase is also an enzyme found in marine bacteria. For example, the marine bacterium Ochrovirga pacifica produces acetyl xylan esterase. This acetyl xylan esterase is known to maintain activity for 120 minutes at a temperature of 45°C (Microbial cell factories 2019Jul08 Vol. 18 issue(1)).
[0029] The present inventors have studied the use of this acetyl xylan esterase in the biodegradation of cellulose acetate. In the study, they have found that acetyl xylan esterase is an esterase, and that cellulose acetate with low substituents at the 2- and 3-positions is particularly susceptible to degradation by acetyl xylan esterase. Furthermore, they have found that, for cellulose acetates with the same total degree of substitution, those with a lower degree of substitution at the 2- and 3-positions are advantageous in terms of biodegradability, particularly biodegradability in the ocean, and have arrived at the present disclosure.
[0030] From another perspective, it is known that marine algae are weakly basic, and this basicity promotes deacetylation of cellulose acetate. As a result of investigations, the present inventors have found that deacetylation (hydrolysis) under basic conditions is promoted in cellulose acetate in which acetyl groups are nonuniformly introduced to the carbon atoms at the 2-, 3-, and 6-positions of the glucose ring. Furthermore, they have found that the action of β-glucosidase becomes easier when the glucose rings in which the substituents at the 2- and 3-positions are hydrolyzed are continuous, and have arrived at the present disclosure.
[0031] The cellulose acetate of the present disclosure has a total acetyl substitution degree of 1.75 to 2.55, and at least one of the acetyl substitution degree at the 2-position and the acetyl substitution degree at the 3-position is 0.7 or less. In this cellulose acetate, the substitution degrees at the 2-position, 3-position, and 6-position are not uniform. The cellulose acetate of the present disclosure, which has a low substitution degree at least at the 2-position or the 3-position, promotes deacetylation under basic conditions. It is believed that this promotion effect reduces the total substitution degree of the cellulose acetate, thereby achieving a high biodegradation rate in seawater.
[0032] The degree of acetyl substitution at the 2-position and the 3-position is not particularly limited, as long as either one is 0.7 or less. For example, when the degree of acetyl substitution at the 2-position is 0.7 or less, the degree of acetyl substitution at the 3-position may be 1.0 or less, 0.9 or less, or 0.8 or less. Similarly, when the degree of acetyl substitution at the 3-position is 0.7 or less, the degree of acetyl substitution at the 2-position may be 1.0 or less, 0.9 or less, or 0.8 or less. From the viewpoint of ease of production, the degree of acetyl substitution at the 2-position or the 3-position is preferably 0.1 or less.
[0033] In order to improve biodegradability in seawater, the degree of acetyl substitution at the 2-position or the degree of acetyl substitution at the 3-position is preferably 0.6 or less, more preferably 0.5 or less, and both of them are preferably 0.7 or less, more preferably 0.6 or less, and particularly preferably 0.5 or less.
[0034] There is no particular limitation on the degree of acetyl substitution at the 6-position, and it is adjusted so as to satisfy the range of the total degree of acetyl substitution described below.
[0035] The degree of acetyl substitution at the 2nd, 3rd and 6th positions of the glucose ring of cellulose acetate can be measured by NMR according to the method of Tezuka (Tezuka, Carbonydr. Res. 273, 83 (1995)). That is, the free hydroxyl groups of a cellulose acetate sample are propionylated with propionic anhydride in pyridine. The obtained sample is dissolved in deuterated chloroform and13 The C-NMR spectrum is measured. The carbon signals of the acetyl group appear in the region from 169 ppm to 171 ppm in the order of 2nd, 3rd, and 6th positions from the high magnetic field, and the signals of the carbonyl carbon of the propionyl group appear in the same order in the region from 172 ppm to 174 ppm. From the abundance ratio of the acetyl group and the propionyl group at the corresponding positions (in other words, the area ratio of each signal), the degree of acetyl substitution at the 2nd, 3rd, and 6th positions of the glucose ring in the original cellulose acetate can be calculated. The degree of acetyl substitution is 13 In addition to C-NMR, 1 It can also be analyzed by H-NMR.
[0036] From the viewpoint of improving biodegradability, the total acetyl substitution degree of cellulose acetate is preferably 2.40 or less, and more preferably 2.20 or less. From the viewpoint of ease of molding, the total acetyl substitution degree of cellulose acetate is preferably 1.85 or more, and more preferably 2.00 or more. The total acetyl substitution degree of cellulose acetate may be 1.75 to 2.40, 1.75 to 2.20, 1.85 to 2.55, 1.85 to 2.40, 1.85 to 2.20, 2.00 to 2.55, 2.00 to 2.40, or 2.00 to 2.20.
[0037] The total degree of acetyl substitution in the present disclosure is the sum of the degrees of acetyl substitution at the 2-, 3-, and 6-positions of the glucose ring of cellulose acetate, which is determined by the above-mentioned measurement method.
[0038] [Viscosity average degree of polymerization (DPv) of cellulose acetate] The viscosity average degree of polymerization (DPv) of the cellulose acetate of the present disclosure is not particularly limited, but from the viewpoint of improving degradability, it is preferably 400 or less, more preferably 300 or less, and even more preferably 200 or less. From the viewpoint of ease of molding, the viscosity average degree of polymerization is preferably 10 or more, more preferably 15 or more, and particularly preferably 20 or more. The viscosity average degree of polymerization (DPv) may be 10 to 400, 10 to 300, 10 to 200, 15 to 40, 15 to 300, 15 to 200, 20 to 400, 20 to 300, or 20 to 200.
[0039] The viscosity average degree of polymerization (DPv) is the intrinsic viscosity number ([η], unit: cm 3 / g).
[0040] Intrinsic viscosity number ([η], unit: cm 3 / g) can be calculated in accordance with JIS-K-7367-1 and ISO 1628-1. Specifically, a sample solution using dimethyl sulfoxide (DMSO) as a solvent is prepared, and the logarithmic relative viscosity at 25°C measured using a size 1C Ubbelohde viscometer is divided by the concentration of the sample solution.
[0041] Using the obtained limiting viscosity number [η], the viscosity average molecular weight was calculated according to the following formula in accordance with the literature by Kamide et al. (Polymer Journal, 13, 421-431 (1981)). Viscosity average molecular weight = (limiting viscosity number [η] / 0.171) (1 / 0.61)
[0042] Using the calculated viscosity average molecular weight, the viscosity average degree of polymerization (DPv) was calculated according to the following formula. Viscosity average degree of polymerization (DPv) = viscosity average molecular weight / (162.14+42.037×DS) In the formula, DS is the total degree of acetyl substitution described above.
[0043] [Amount of sulfuric acid in cellulose acetate] From the viewpoint of improving biodegradability in seawater, the amount of sulfuric acid in the cellulose acetate of the present disclosure is preferably 10 ppm or more, more preferably 20 ppm or more. From the viewpoint of ease of production, the amount of sulfuric acid is preferably 100 ppm or less, more preferably 80 ppm or less, and particularly preferably 50 ppm or less. The amount of sulfuric acid is preferably 10 ppm or more and 100 ppm or less, more preferably 20 ppm or more and 80 ppm or less, and particularly preferably 20 ppm or more and 50 ppm or less, with 36 ppm as the median. The amount of sulfuric acid in the cellulose acetate may be 10 to 80 ppm, 10 to 50 ppm, or 20 to 100 ppm.
[0044] The amount of sulfuric acid in cellulose acetate is measured by the following method. First, dried cellulose acetate is weighed and then baked in an electric furnace at 1300°C, and the sulfurous acid gas generated is trapped in 10% hydrogen peroxide solution. This trapped liquid is titrated with a normal aqueous sodium hydroxide solution. From the titration value obtained, the amount of sulfuric acid in the cellulose acetate is calculated as the amount of H2SO4 per bone-dried cellulose acetate, and expressed in ppm (by weight).
[0045] [Method of producing cellulose acetate] The method of production is not particularly limited as long as the total acetyl substitution degree of the obtained cellulose acetate is 1.75 to 2.55 and at least one of the acetyl substitution degree at the 2-position and the acetyl substitution degree at the 3-position is 0.7 or less. The cellulose acetate may be produced by hydrolysis of cellulose acetate having an appropriate substitution degree produced by a conventional production method as a starting material.
[0046] For example, the cellulose acetate of the present disclosure can be obtained by dissolving cellulose acetate in dimethyl sulfoxide (DMSO) / water / α-amine (e.g., dimethyleneamine or hexamethyleneamine) and hydrolyzing it. The degree of hydrolysis at the 2- and 3-positions varies depending on the type of α-amine used. For example, in the case of hexamethylenediamine (NH2(CH2)6NH2), the acetyl group at the 3-position is preferentially hydrolyzed. In the case of dimethyleneamine (HN(CH3)2), the acetyl group at the 2-position is preferentially hydrolyzed. Furthermore, the 2- and 3-positions are preferentially hydrolyzed by adding an approximately 0.1N sodium hydroxide / acetone / aqueous solution and heating to 40° C. to 80° C. The higher the hydrolysis temperature, the more preferable it is, and it may be 80° C. or higher, but is preferably 100° C. or lower.
[0047] Alternatively, the cellulose acetate of the present disclosure may be obtained by a known method of acetylating the cellulose acetate in a state where a known protecting group is bound to at least one of the carbon at the 2-position or the carbon at the 3-position, and then deprotecting the cellulose acetate. Representative examples of the techniques disclosed in Mokuzai Gakkaishi, vol. 60, pp. 144-168 (2014), Biomacromolecules, 13, pp. 2195-2201 (2012), Carbohydrate Polymer, 170, 23 (2017), etc. may be referenced.
[0048] [Cellulose acetate composition] The cellulose acetate composition according to the present disclosure contains the above-mentioned cellulose acetate and an additive selected from the group consisting of the following (a) to (c): (a) A substance whose pH in a 1% by weight aqueous solution at 20°C is 8 or higher (b) A substance that dissolves at least 2% by weight in water at 20°C and (c) Substances that are biodegradable in seawater
[0049] The substance (a), whose 1 wt % aqueous solution has a pH of 8 or more at 20°C, promotes the hydrolysis (deacetylation) of cellulose acetate in weakly alkaline seawater, which is believed to contribute to improving the biodegradability of the cellulose acetate composition.
[0050] Furthermore, the substance (b) that dissolves at 2% by weight or more in water at 20°C dissolves when the cellulose acetate composition is put into seawater and dissolves from the cellulose acetate composition. The substance (c) that exhibits biodegradability in seawater gradually dissolves from the cellulose acetate composition as the cellulose acetate composition biodegrades from the time the cellulose acetate composition is put into seawater. This dissolution forms structural voids in the molded article made of the cellulose acetate composition, and the substantial surface area of the molded article increases. The increase in surface area promotes hydrolysis (deacetylation) of cellulose acetate in seawater and also makes it easier for microorganisms to invade through the voids, which is thought to improve the biodegradability of the cellulose acetate composition.
[0051] The action of the additive in the cellulose acetate composition is preferably not manifested during use as a product, but is manifested promptly after contact with seawater. Therefore, if the additive is solid, it is preferred that it is dispersed in the cellulose acetate composition in the form of particles, the particle size of which is preferably as small as possible, and the specific surface area of which is preferably large.
[0052] [Cellulose acetate content] From the viewpoint of exhibiting high biodegradability in seawater, the content of the cellulose acetate of the present disclosure in the cellulose acetate composition is preferably 50% by weight or more, more preferably 55% by weight or more, based on the entire composition. From the viewpoint of effectively exhibiting the decomposition-promoting effect of the additive, the content of the cellulose acetate is preferably 90% by weight or less, more preferably 85% by weight or less. The content of the cellulose acetate in the composition of the present disclosure may be 50 to 90% by weight, 50 to 85% by weight, 55 to 90% by weight, or 55 to 85% by weight. When two or more types of cellulose acetate having different physical properties are used in combination, the total amount is adjusted to the above-mentioned numerical range.
[0053] [Amount of additives added] From the viewpoint of contributing to improvement of biodegradability, the total amount of additives added in the cellulose acetate composition according to the present disclosure is preferably 3% by weight or more, more preferably 5% by weight or more, based on the entire composition. From the viewpoint of ease of molding, the total amount of additives added is preferably 40% by weight or less, more preferably 35% by weight or less. The total amount of additives added in the composition according to the present disclosure may be 3 to 40% by weight, 3 to 35% by weight, 5 to 40% by weight, or 5 to 35% by weight. When a plurality of additives are used in combination, the total amount is adjusted to the above-mentioned numerical range.
[0054] [Content of cellulose acetate and additives] From the viewpoint of obtaining excellent biodegradability, the total content of the cellulose acetate and the additives in the cellulose acetate composition according to the present disclosure is preferably 85% by weight or more, more preferably 90% by weight or more, and particularly preferably 95% by weight or more. The upper limit of this total content is not particularly limited, and may be 100% by weight.
[0055] [Substance (a) having a pH of 8 or more in a 1% by weight aqueous solution at 20°C] A substance having a pH of 8 or more in a 1 wt % aqueous solution at 20° C. is also called a basic additive. The basic additive preferably has a pH of 8.5 or more in a 1 wt % aqueous solution at 20° C., more preferably 8.5 to 11. The pH of a 1 wt % aqueous solution is measured according to known procedures, for example with a glass pH electrode.
[0056] In this disclosure, the term "aqueous solution" does not only mean a state in which all solutes are dissolved in water, but is a concept that includes suspension. This "suspension" includes a slurry, which is a dispersion system in which solid particles are dispersed in a liquid, and a colloidal solution. Furthermore, in this disclosure, a "1 wt % aqueous solution" also includes a solution in which, when a basic additive is added to water to a concentration of 1 wt %, part of the basic additive dissolves to form an aqueous solution, and the remaining part of the basic additive forms a suspension.
[0057] Preferably, the substance (a) having a pH of 8 or more at 20° C. in a 1% by weight aqueous solution is selected from the group consisting of the following (a1)-(a3): (a1) An inorganic compound containing an oxygen atom bonded to any one of the metal elements Na, K, Ca, or Mg. (a2)Na + , K + , Ca 2+ or Mg 2+ and one or more anions selected from carbonate ions, hydrogen carbonate ions, silicate ions, and aluminate ions. and (a3) Inorganic compounds containing magnesium
[0058] In particular, the cellulose acetate composition containing an additive selected from inorganic compound (a1) and metal salt (a2) has a significantly improved seawater biodegradability. This is believed to be because the inorganic compound (a1) and metal salt (a2) exhibit basicity in seawater, thereby significantly promoting the hydrolysis of cellulose acetate. From this viewpoint, a composition containing at least one additive selected from (a1) and (a2) is preferred. The cellulose acetate composition of the present disclosure may contain, as other basic substances, basic polymers and oligomers; basic amino acids and proteins; and basic sugars.
[0059] Examples of the inorganic compound (a1) containing an oxygen atom bonded to any one of the metal elements Na, K, Ca, and Mg include oxides, hydroxides, and composite oxides of any one of the metal elements Na, K, Ca, and Mg. From the viewpoints of improving biodegradability and easy handling, preferred inorganic compounds (a1) are magnesium oxide, magnesium hydroxide, talc, hydrotalcite, bentonite, calcium oxide, and calcium hydroxide.
[0060] Na + , K + , Ca 2+ or Mg 2+ Examples of the metal salt (a2) containing one or more metal ions selected from the above and one or more anions selected from carbonate ions, hydrogen carbonate ions, silicate ions, or aluminate ions include sodium carbonate, potassium carbonate, calcium carbonate, magnesium carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, calcium hydrogen carbonate, magnesium hydrogen carbonate, calcium silicate, magnesium silicate, magnesium aluminate, and magnesium aluminometasilicate.
[0061] Sodium aluminate includes sodium aluminum dioxide (NaAlO2), which is a double oxide, and sodium aluminate tetrahydroxide (Na[Al(OH)4], which is a hydroxy complex. Magnesium aluminometasilicate is a substance represented by the general formula Al2O3·MgO·2SiO2·xH2O (where x represents the number of crystal waters, and 1≦x≦10). As magnesium aluminometasilicate, for example, magnesium aluminometasilicate in accordance with the Japanese Pharmacopoeia Non-Drug Standards can be suitably used. Silicic acid is a compound represented by the general formula [SiO x (OH) 4-2x ] n It is a general term for compounds of silicon, oxygen, and hydrogen represented by the formula:
[0062] From the viewpoint of obtaining high biodegradability and good moldability, preferred metal salts (a2) are calcium carbonate, magnesium carbonate, calcium silicate, magnesium silicate, magnesium aluminate, and magnesium aluminometasilicate.
[0063] An example of the magnesium-containing inorganic compound (a3) is magnesium oxide. The magnesium-containing inorganic compound (a3) is preferably mainly composed of magnesium oxide.
[0064] Magnesium oxide is an oxide of magnesium represented by the chemical formula MgO, and is also called milk of magnesia. Magnesium oxide may contain trace amounts of each of the elements Al, Si, P, Mn, Fe, Ni, Cu, and Zn. Here, trace amounts means less than 1000 ppm, preferably less than 100 ppm.
[0065] In the present disclosure, there is no particular limitation on the method for producing magnesium oxide, but it may be a method of producing it by calcining and pulverizing natural magnesium carbonate ore (MgCO3) in dolomite (CaCO3·MgCO3), or a method of precipitating magnesium ions in seawater as hydroxide (Mg(OH)2) and dehydrating it at high temperature.
[0066] [Substance (b) that dissolves at 2% by weight or more in water at 20°C] The substance (b) that dissolves at 2% by weight or more in water at 20° C. may be a polymeric or low molecular weight substance as long as it is water-soluble. Preferably, the substance (b) that dissolves at 2% by weight or more in water at 20° C. is selected from the group consisting of the following (b1)-(b3): (b1) Glycerin ester (b2) Citric acid esters and (b3) Polyethylene glycol having a number average degree of polymerization of 20 or less
[0067] The glycerin ester (b1), the citrate ester (b2), and the polyethylene glycol (b3) having a number average degree of polymerization of 20 or less also act as plasticizers for cellulose acetate. Therefore, the cellulose acetate composition containing these as additives is easily melt moldable.
[0068] The glycerol ester (b1) is a compound in which at least one hydroxyl group of glycerol is esterified, and is preferably a compound esterified with a carboxylic acid having a molecular weight of 150 or less, more preferably a compound esterified with a carboxylic acid having a molecular weight of 130 or less. The glycerol ester (b1) may be a compound in which all three hydroxyl groups of glycerol are esterified with the same carboxylic acid, a compound in which two hydroxyl groups of glycerol are esterified with the same carboxylic acid, or a compound in which all three hydroxyl groups of glycerol are esterified with different carboxylic acids.
[0069] The carboxylic acid may be an aliphatic carboxylic acid (fatty acid) or an aromatic carboxylic acid. Fatty acids are preferred from the viewpoint of reducing the burden on the environment. They may be saturated or unsaturated fatty acids. A preferred glycerin ester (b1) is esterified with a saturated fatty acid. Specific examples of saturated fatty acids include formic acid, acetic acid, propionic acid, and butyric acid. A more preferred glycerin ester (b1) is glycerin acetate having an acetyl substitution degree of 0 to 3, and particularly preferred is triacetin (glycerol trisacetate) in which all three hydroxyl groups of glycerin are esterified with acetic acid (in other words, acetylated).
[0070] Triacetin is a component that is recognized as safe for human ingestion and is easily biodegradable, so it places little strain on the environment. In addition, the cellulose acetate composition obtained by adding triacetin to cellulose acetate has improved biodegradability compared to the case where cellulose acetate is used alone. Furthermore, by adding triacetin to cellulose acetate, the glass transition temperature of cellulose acetate can be efficiently lowered. Therefore, excellent thermoformability can be imparted to the raw material.
[0071] The citric acid ester (b2) is a compound in which at least one carboxyl group of citric acid is esterified. The citric acid ester (b2) may be one in which all three carboxyl groups of citric acid are esterified with the same hydrocarbon group, one in which two carboxyl groups of citric acid are esterified with the same hydrocarbon group, or one in which all three carboxyl groups of glycerin are esterified with different hydrocarbon groups.
[0072] The hydrocarbon group may be linear, branched, or cyclic. An aliphatic hydrocarbon group is preferred, and a saturated aliphatic hydrocarbon group (alkyl group) is more preferred. Specific examples of the alkyl group include a methyl group, an ethyl group, and a propyl group. Preferred examples of the citrate ester (b2) include triethyl citrate and acetyltriethyl citrate.
[0073] Polyethylene glycol (b3) having a number-average degree of polymerization of 20 or less has an ethyleneoxy group as a repeating unit. The degree of polymerization is the number of repeating units. Polyethylene glycol (b) having a number-average degree of polymerization of 20 or less is easily soluble in seawater, and can contribute to improving biodegradability. From this viewpoint, the number-average degree of polymerization of polyethylene glycol is more preferably 18 or less, and particularly preferably 15 or less. From the viewpoint of suppressing bleed-out when molded into a molded article, the number-average degree of polymerization of polyethylene glycol is preferably 2 or more, and more preferably 3 or more. The number-average degree of polymerization is calculated from the number-average molecular weight measured by size exclusion chromatography (GPC) using polystyrene as a standard substance.
[0074] [Substances that are biodegradable in seawater (c)] Examples of substances (c) that are biodegradable in seawater include substances that decompose by 50% by weight or more, preferably 70% by weight or more, and more preferably 90% by weight or more, of the comparable cellulose after 120 days according to the method specified in ASTM D6691.
[0075] The substance (c) that is biodegradable in seawater is, for example, a polyester having a weight-average molecular weight of 50,000 or less. A polyester selected from the group consisting of polyhydroxybutyrate, poly(3-hydroxybutyrate-co-3-hydroxyhexanoate), polybutylene succinate, polycaprolactone, and polyglycolic acid is preferred.
[0076] [Preferable combination of additives] From the viewpoint of improving biodegradability, the cellulose acetate composition of the present disclosure preferably contains an additive selected from magnesium oxide, magnesium aluminometasilicate, and triacetin. From the viewpoint of improving biodegradability and easy molding, the cellulose acetate composition of the present disclosure preferably contains at least one selected from magnesium oxide and magnesium aluminometasilicate, and triacetin. An additive consisting of a combination of magnesium oxide and triacetin is more preferred.
[0077] [Method for producing cellulose acetate composition] The cellulose acetate composition of the present disclosure is obtained by mixing cellulose acetate having a total acetyl substitution degree of 1.75 to 2.55 and at least one of the acetyl substitution degree at the 2-position and the acetyl substitution degree at the 3-position being 0.7 or less with the above-mentioned additive in a solvent such as acetone, and then removing the solvent. The cellulose acetate composition of the present disclosure may be obtained by melt-kneading. Preferably, this composition is obtained by mixing cellulose acetate and additives, and then melt-kneading. By mixing before melt-kneading, the additives and cellulose acetate are more uniformly blended in a short time, and the resulting kneaded product is homogenized, so that a composition with improved melt flowability and processing accuracy can be obtained.
[0078] A known mixer such as a Henschel mixer can be used to mix the cellulose acetate and the additives. Dry mixing or wet mixing may be used. When using a mixer such as a Henschel mixer, the temperature inside the mixer is preferably a temperature at which the cellulose acetate does not melt, for example, 20°C or higher and lower than 200°C.
[0079] An extruder such as a twin-screw extruder can be used for melt-kneading the cellulose acetate and the additives, or for melt-kneading after mixing the cellulose acetate and the additives. From the viewpoint of uniformity of the kneaded product and suppression of heat deterioration, the kneading temperature (cylinder temperature) of the extruder is preferably 170°C or more and 230°C or less. For example, when melt-kneading is performed using a twin-screw extruder, the kneading temperature (also called the cylinder temperature) may be 200°C. The kneaded product may be extruded in a strand shape from a die attached to the tip of the twin-screw extruder, and then hot-cut into pellets. In this case, the die temperature may be about 220°C.
[0080] The amount of additives added to the entire cellulose acetate composition obtained is preferably 3% by weight or more and 40% by weight or less. When two or more kinds of additives are blended, the total amount is adjusted to 3% by weight or more and 40% by weight or less.
[0081] The amount of cellulose acetate in the entire cellulose acetate composition is preferably 50% by weight or more, more preferably 50% by weight or more and 90% by weight or less. When two or more kinds of cellulose acetates are mixed, the total amount is adjusted to be preferably 50% by weight or more, more preferably 50% by weight or more and 90% by weight or less.
[0082] The cellulose acetate composition may contain additives other than those mentioned above, as long as they do not inhibit the biodegradability of the composition. Examples of the additives include colorants, ultraviolet absorbers, light stabilizers, antioxidants, heat stabilizers, optical property adjusters, fluorescent brighteners, and flame retardants. In this case, it is preferable to add the cellulose acetate and additives so that the total content of the cellulose acetate and additives in the cellulose acetate composition is 85% by weight or more.
[0083] The cellulose acetate of the present disclosure has excellent melt moldability, so it is also suitable for melt molding.The shape of the molded product obtained by molding the cellulose acetate composition of the present disclosure is not particularly limited, and can be, for example, one-dimensional molded product such as fiber; two-dimensional molded product such as film; and three-dimensional molded product such as particulate, tube and hollow cylinder including pellet.
[0084] The cellulose acetate or cellulose acetate composition disclosed herein has excellent biodegradability in seawater, and is therefore suitable for products that are easily disposable, such as containers such as straws and cups, packaging materials, binders, and cigarette filters; clothing fibers; nonwoven fabrics; cosmetic beads and scrubs, and other products that are likely to be washed away, even if only partially, into the natural environment with water when used; and sanitary products (diapers, sanitary products), and other products that are expected to be flushed down the toilet. EXAMPLES
[0085] The effects of the present disclosure will be clarified by the following examples. Each configuration and their combinations in each embodiment are merely examples, and addition, omission, substitution, and other modifications of the configurations are possible as appropriate within the scope of the gist of the present disclosure. The present disclosure is not limited by the embodiments, but only by the scope of the claims. Unless otherwise specified, all test temperatures are room temperature (20°C ± 5°C).
[0086] [Example 1] The cellulose acetate of Example 1 was synthesized with reference to Mokuzai Gakkaishi, vol. 60, pp. 144-168 (2014) and Biomacromolecules, 13, pp. 2195-2201 (2012).
[0087] First, 100.4 g of cellulose (linters raw material) was added to 3 L of 18 wt% NaOH aqueous solution and stirred at room temperature for 1 hour. After that, the cellulose was collected by filtration and washed with water until the washing liquid became neutral. Next, the cellulose was added to 500 mL of dimethylacetamide and stirred at room temperature for 12 hours, and then the cellulose was filtered and washed twice with 500 mL of dimethylacetamide.
[0088] Next, this cellulose was added to 4 L of dimethylacetamide, heated at 150° C. for 1 hour, and then cooled until the liquid temperature reached 100° C. After that, 350 g of anhydrous lithium chloride was added, stirred at 100° C. for 1 hour, and cooled to 25° C., thereby dissolving the cellulose in a lithium chloride / dimethylacetamide (DMAC)-based solvent.
[0089] To the resulting cellulose solution, 200 g of imidazole and 450 g of thexyldimethylsilyl chloride (1,1,2-trimethylpropyl dimethyl silyl chloride) were added and reacted to obtain cellulose in which the 2- and 6-positions were silyl-etherified. The crude product was washed three times with 1.5 L of methanol to obtain 268.0 g of 2,6-silyl-etherified cellulose.
[0090] The obtained 265.5 g of 2,6-silyl etherified cellulose was dissolved in 2000 g of dimethylacetamide and 165.9 g of pyridine, and then reacted with 142.2 g of allyl chloride. The obtained reaction solution was added to methanol to cause precipitation, and the precipitate (crude product) was washed three times with 1.0 L of methanol to obtain 265.5 g of product. This product was dissolved in 4000 g of dimethylacetamide and reacted with 380 g of tetrabutylammonium fluoride to obtain 77.7 g of cellulose with allyl etherification at the 3-position.
[0091] 77.7 g of the obtained 3-allyl cellulose was dissolved in 800 g of dimethylacetamide, and 167 g of acetic anhydride and 136 g of pyridine were added and reacted to obtain 2,6-acetyl-3-allyl cellulose. Then, 4.9 g of tetrakistriphenylphosphine palladium was added to isomerize the allyl ether group, and the allyl group was deprotected by reacting with K2CO3 to obtain 73.2 g of cellulose acetate of Example 1, in which the 2- and 6-positions were selectively substituted. The free hydroxyl groups of the cellulose acetate were propionylated by the above-mentioned method, and the cellulose acetate was dissolved in deuterated chloroform. 13 The degrees of substitution at the 2-, 3- and 6-positions were confirmed by measuring the C-NMR spectrum. The results are shown in Table 1 below as DS2, DS3 and DS6, respectively. The total degree of acetyl substitution is the sum of the degrees of acetyl substitution at the 2-, 3- and 6-positions. The cellulose acetate of Example 1 had DS2=0.98, DS3=0.47 and DS6=1.00, and the total degree of acetyl substitution was 2.45.
[0092] 10 parts by weight of the cellulose acetate of Example 1 obtained was dried by heating at 110° C. for 2 hours, then added to 90 parts by weight of acetone and stirred at 25° C. for 6 hours to dissolve the cellulose acetate, thereby preparing a dope for film production. The dope was poured onto a glass plate, cast with a bar coater, and dried at 40° C. for 30 minutes, after which the film was peeled off from the glass plate and further dried at 80° C. for 30 minutes to obtain the cellulose acetate film of Example 1 (thickness 30 μm).
[0093] [Example 2] Cellulose acetate of Example 2 was synthesized with reference to JP2015-224256A.
[0094] First, 50 g of cellulose acetate (acetyl substitution degree 2.87) was dissolved in 500 g of N-methylpyrrolidone. Next, 57 g of cesium carbonate was added, and the mixture was stirred at room temperature for 10 hours to react. An appropriate amount of water was added to the resulting reaction solution to cause precipitation, and the precipitate was washed with methanol and dried to obtain 37.8 g of cellulose acetate of Example 2. In the same manner as in Example 1, 1 The degrees of substitution at the 2-, 3- and 6-positions were confirmed by measuring the H-NMR spectrum. The results are shown in Table 1 below. The cellulose acetate of Example 2 had DS2=0.65, DS3=0.75, and DS6=0.83, and the total degree of acetyl substitution was 2.23.
[0095] Using the obtained cellulose acetate, a cellulose acetate film of Example 2 (thickness: 30 μm) was obtained in the same manner as in Example 1.
[0096] [Example 3]
[0097] First, 4.5 g of cellulose made of linter pulp was dissolved in 75 g of 1-butyl-3-methylimidazolium chloride. Next, acetic anhydride was added in an amount of 4.9 times (13.8 g) the molar amount of the cellulose skeleton, and the mixture was reacted at 80° C. for 1 hour. After that, an appropriate amount of methanol was added to the resulting reaction solution to cause precipitation, and the precipitate was washed with methanol and dried to obtain 5.44 g of cellulose acetate of Example 3. In the same manner as in Example 1, 1 The degrees of substitution at the 2-, 3- and 6-positions were confirmed by measuring the H-NMR spectrum. The results are shown in Table 1 below. The cellulose acetate of Example 3 had DS2 = 0.49, DS3 = 0.66, and DS6 = 0.95, and the total degree of acetyl substitution was 2.10.
[0098] Using the obtained cellulose acetate, a cellulose acetate film of Example 3 (thickness: 30 μm) was obtained in the same manner as in Example 1.
[0099] [Example 4] The cellulose acetate of Example 1 was synthesized with reference to Mokuzai Gakkaishi, vol. 60, pp. 144-168 (2014) and Biomacromolecules, 13, pp. 2195-2201 (2012).
[0100] First, 100.4 g of the cellulose described in Example 1-3 was added to 3 L of an aqueous NaOH solution with a concentration of 18% by weight, and stirred at room temperature for 1 hour. Then, the solid matter (alkali cellulose) was collected by filtration, and washed with water until the washing liquid became neutral. Next, this cellulose was added to 500 mL of dimethylacetamide, and stirred at room temperature for 12 hours, and then the cellulose extracted by filtration was washed twice with 500 mL of dimethylacetamide.
[0101] Next, this cellulose was added to 4 L of dimethylacetamide, heated at 150° C. for 1 hour, and then cooled until the liquid temperature reached 100° C. After that, 350 g of anhydrous lithium chloride was added, stirred at 100° C. for 1 hour, and cooled to 25° C., thereby dissolving the cellulose in a lithium chloride / dimethylacetamide (DMAC)-based solvent.
[0102] To the resulting cellulose solution, 200 g of imidazole and 237.2 g of thexyldimethylsilyl chloride (1,1,2-trimethylpropyl dimethyl silyl chloride) were added and reacted to obtain cellulose in which the 2- and 6-positions were silyl-etherified. The crude product was washed three times with 1.5 L of methanol to obtain 168.0 g of 2,6-silyl-etherified cellulose.
[0103] The entire amount of the obtained 2,6-silyl etherified cellulose was dissolved in 800 g of dimethylacetamide, and 387.6 g of acetic anhydride and 316 g of pyridine were added and reacted to acetylate the remaining hydroxyl groups. 1.5 L of methanol was added to the obtained reaction solution to obtain a precipitate. The precipitate was collected by filtration and then washed three times with 500 mL of methanol to obtain 203 g of product.
[0104] The resulting product was dissolved in 4 L of dimethyl sulfoxide and reacted with 469 g of tetrabutylammonium fluoride to remove the silyl ether group, thereby obtaining 82.4 g of cellulose acetate of Example 4. 1 The degrees of substitution at the 2-, 3- and 6-positions were confirmed by measuring the H-NMR spectrum. The results are shown in Table 1 below. The cellulose acetate of Example 4 had DS2 = 0.42, DS3 = 1.00, and DS6 = 0.46, and the total degree of acetyl substitution was 1.88.
[0105] Using the obtained cellulose acetate, a cellulose acetate film of Example 4 (thickness: 30 μm) was obtained in the same manner as in Example 1.
[0106] [Comparative Example 1] Hardwood prehydrolyzed kraft pulp with an α-cellulose content of 98.4 wt% was crushed into a cotton-like state using a disc refiner. 26.8 parts by weight of acetic acid was sprayed onto 100 parts by weight of the crushed pulp (water content 8%), and after thorough mixing, the mixture was left to stand for 60 hours as a pretreatment for activation. The activated pulp was added to a mixture of 323 parts by weight of acetic acid, 245 parts by weight of acetic anhydride, and 13.1 parts by weight of sulfuric acid, and the temperature was adjusted from 5°C to a maximum of 40°C over 40 minutes, and the mixture was acetylated for 90 minutes. A neutralizing agent (24% magnesium acetate aqueous solution) was added over 3 minutes so that the amount of sulfuric acid (amount of aged sulfuric acid) was adjusted to 2.5 parts by weight. Furthermore, after the reaction bath was heated to 75°C, water was added to adjust the reaction bath moisture (aging moisture) to a concentration of 52 mol%. The aging moisture concentration was expressed in mol% by multiplying the ratio of the reaction bath moisture to acetic acid expressed in molar ratio by 100. The mixture was then aged at 85°C for 100 minutes, and the aging was stopped by neutralizing the sulfuric acid with magnesium acetate to obtain a reaction mixture containing cellulose acetate. A dilute aqueous solution of acetic acid was added to the reaction mixture to separate the cellulose acetate, which was then washed with water, dried, and stabilized with calcium hydroxide to obtain the cellulose acetate of Comparative Example 1.
[0107] In the same manner as in Example 1 13The degrees of substitution at the 2-, 3- and 6-positions were confirmed by measuring the C-NMR spectrum. The results are shown in Table 1 below. The cellulose acetate of Comparative Example 1 had DS2 = 0.86, DS3 = 0.85, and DS6 = 0.75, and the total degree of acetyl substitution was 2.46.
[0108] Using the obtained cellulose acetate, a cellulose acetate film (thickness: 30 μm) of Comparative Example 1 was obtained in the same manner as in Example 1.
[0109] [Examples 5, 10, 15 and 20] 9.5 parts by weight of cellulose acetate of Examples 1-4 were each heated at 110°C for 2 hours and dried, then added to 90 parts by weight of acetone, and stirred at 25°C for 6 hours to dissolve the cellulose acetate. 0.5 parts by weight of magnesium aluminometasilicate powder was added thereto as an additive, and further stirred at 25°C for 6 hours to prepare a dope for film production. This dope was poured onto a glass plate, cast with a bar coater, dried at 40°C for 30 minutes, and then peeled off the film from the glass plate and dried at 80°C for another 30 minutes to obtain the cellulose acetate composition films (thickness 30 μm) of Examples 5, 10, 15 and 20.
[0110] [Examples 6, 11, 16 and 21] Cellulose acetate composition films (thickness 30 μm) of Examples 6, 11, 16 and 21 were obtained in the same manner as in Examples 5, 10, 15 and 20, except that magnesium oxide was used as an additive and 0.4 parts by weight of the additive was added per 9.6 parts by weight of each cellulose acetate.
[0111] [Examples 7, 12, 17, and 22] Cellulose acetate composition films (thickness 30 μm) of Examples 7, 12, 17, and 22 were obtained in the same manner as in Examples 5, 10, 15, and 20, except that triacetin was used as the additive and 2.0 parts by weight of the additive was added to 8.0 parts by weight of each cellulose acetate.
[0112] [Examples 8, 13, 18 and 23] The cellulose acetate composition films (thickness 30 μm) of Examples 8, 13, 18 and 23 were obtained in the same manner as in Examples 5, 10, 15 and 20, except that magnesium aluminometasilicate and triacetin were used as additives, and 0.5 parts by weight of magnesium aluminometasilicate and 2.0 parts by weight of triacetin were added to 7.5 parts by weight of each cellulose acetate.
[0113] [Examples 9, 14, 19 and 24] The cellulose acetate composition films (thickness 30 μm) of Examples 9, 14, 19 and 24 were obtained in the same manner as in Examples 5, 10, 15 and 20, except that magnesium oxide and triacetin were used as additives, and 0.4 parts by weight of magnesium oxide and 2.0 parts by weight of triacetin were added to 7.6 parts by weight of each cellulose acetate.
[0114] [Evaluation of marine biodegradability] According to the following procedure, the cellulose acetate films of Examples 1-4 and Comparative Example 1 and the cellulose acetate composition films of Examples 5-24 were each pulverized to an average particle size of about 20 μm, and then subjected to the biodegradation test described below.
[0115] 60 mg of each sample was added to 250 g of seawater and stirred at 30°C. The amount of carbon dioxide generated was measured 90 days and 120 days after the sample was added. The theoretical amount of carbon dioxide generated was calculated from the total organic carbon (TOC) measured for each sample used in the test, and the ratio of the measured value minus the blank (seawater only) measured value to this theoretical amount of carbon dioxide generated was taken as the degree of biodegradation (%). The results are shown in Tables 1 and 2 below.
[0116] [Table 1]
[0117] [Table 2]
[0118] As shown in Tables 1 and 2, the cellulose acetate of the examples has a higher decomposition rate in seawater than the cellulose acetate of the comparative examples. Also, the cellulose acetate compositions of the examples contain additives, and thus have an improved decomposition rate in seawater compared to the corresponding cellulose acetate. From these evaluation results, the superiority of the present disclosure is clear. [Industrial Applicability]
[0119] The cellulose acetate and the composition described above are not limited to being in the form of a film, but can be used as biodegradable molded articles in various shapes.
Claims
1. A cellulose acetate having a total degree of acetyl substitution of 1.75 to 2.55 and at least one of a degree of acetyl substitution at the 2-position and a degree of acetyl substitution at the 3-position being 0.7 or less, and an additive; the additive is selected from the group consisting of: (a) a substance having a pH of 8 or more in a 1% by weight aqueous solution at 20° C.; and (b) a substance that dissolves in water at 20° C. at 2% by weight or more; The substance (a) having a pH of 8 or more in a 1 wt % aqueous solution at 20° C. (a1) An inorganic compound containing an oxygen atom bonded to any one of the metal elements Na, K, Ca, or Mg. and (a2) Na + , K + , Ca 2+ Or Mg 2+ and one or more anions selected from carbonate ions, hydrogen carbonate ions, silicate ions, and aluminate ions. is selected from the group consisting of the inorganic compound (a1) containing an oxygen atom bonded to any one of Na, K, Ca, and Mg metal elements is selected from the group consisting of an oxide, a hydroxide, and a composite oxide of any one of Na, K, Ca, and Mg metal elements; The substance (b) that dissolves in water at 20° C. at a rate of 2% by weight or more (b1) Glycerin ester (b2) Citric acid ester and (b3) Polyethylene glycol having a number average degree of polymerization of 20 or less The cellulose acetate composition is selected from the group consisting of:
2. 2. The cellulose acetate composition according to claim 1, wherein the content of the cellulose acetate is 50% by weight or more.
3. 3. The cellulose acetate composition according to claim 1, wherein the total content of the additives is from 3% by weight to 40% by weight.
4. 4. The cellulose acetate composition according to claim 1, wherein the additive comprises a combination of magnesium oxide and triacetin.
5. 5. The cellulose acetate composition according to claim 1, wherein the degree of acetyl substitution at the 2-position and the degree of acetyl substitution at the 3-position of the cellulose acetate are 0.7 or less.
6. 6. The cellulose acetate composition according to claim 1, wherein the cellulose acetate has a total degree of acetyl substitution of 2.00 or more.
7. 7. The cellulose acetate composition according to claim 1, wherein the total degree of acetyl substitution of the cellulose acetate is 2.20 or less.
8. The cellulose acetate composition according to any one of claims 1 to 3, wherein the additive is selected from the group consisting of magnesium oxide, magnesium aluminometasilicate and triacetin.
9. The cellulose acetate composition according to claim 1 , wherein the additive comprises at least one selected from magnesium oxide and magnesium aluminometasilicate, and triacetin.
10. 10. The cellulose acetate composition according to claim 1, wherein a total content of the cellulose acetate and the additive is 85% by weight or more and 100% by weight or less.
Citation Information
Patent Citations
Biodegradable cellulose acetate plastic and preparation method thereof
CN102585297A
Acetyl cellulose resin composition and its production method
JP2002030182A
Process for preparation of cellulose acylate solution and cellulose acylate film
JP2002265501A
Cellulose acylate, resin composition, and resin molded body
JP2018024803A
Polymer composition containing a basic additive, method, and article containing said polymer composition
JP2018500416A